Development of the Multi-Analyte Test for Immune-Chromatographic Detection of Botulinum Toxins - I. V. Shilenko; A. A. Titov; S. P. Yarkov; V. N. Zlobin (Проблемы особо опасных инфекций, 2011)
Designed is the multi-analyte test for simultaneous immune chromatographic detection of A & B type botulinum neurotoxins (BT), using colloid gold nanoparticles. It is meant for food and environmental samples' analysis. The sensitivity of simultaneous BT detection of the A (30 ng/ml) and B (10 ng/ml) types is as high as that of mono-analytical tests, designed for one type BT detection. The test is demonstrated to be a specific one and can be used for BT detection in food stuffs.